Research Competencies to Develop Academic Reading and Writing: A Systematic Literature Review - Castillo-Martínez, Isolda Margarita; Ramírez-Montoya, María Soledad (Frontiers in Education, 2021)
The development of research skills in the higher education environment is a necessity because universities must be concerned about training professionals who use the methods of science to transform reality. An interdisciplinary and transdisciplinary approach that promotes a profile of graduation including research skills that are common to all careers whilst respecting their particularities is now crucial. Furthermore, within research competencies, consideration must be given to those that allow for the development of academic reading and writing in university students since this is a field that requires considerable attention from the educational field at the higher level. This study aims to conduct a systematic review of the literature that allows the analysis of studies related to the topics of research competencies and the development of academic reading and writing. The search was performed by considering the following quality criteria: (1) Is the context in which the research is conducted at higher education institutions? 2) Is the development of academic reading and writing considered? (3) Are innovation processes related to the development of academic reading and writing considered? The articles analysed were published between 2015 and 2019. in a systematic mapping conducted earlier 345 articles were selected, 42 were considered for analysis after following the quality criterion questions. Finally, the topics addressed in the analysis were as follows: theoretical–conceptual trends in educational innovation studies, dominant trends and methodological tools, findings in research competencies for innovation in academic literacy development, types of innovations related to the development of academic reading and writing, recommendations for future studies on research competencies and for the processes of academic reading and writing and research challenges for the research competencies and academic reading and writing processes. This study aims to determine how the three elements present in the quality criteria of this systematic literature review can be linked so that they can serve as a basis for identifying which research competencies can be used to develop academic literacy in higher education contexts through innovative models.